STUDY ON EXPRESS OF α-HCG AND α-HCGmRNA IN PANCREATIC ENDOCRINE TUMORS - Yu, Jiyao; Bordi, Cesare (Chinese Journal of Cancer Research, 2013)
The antigen Alpha-subunit of human chorionic gonadotropin (α-HCG) and ct-HCGmRNA in pancreatic endocrine tumors (PET) were investigated by hnmunohistochemistry and in situ hybridization. It was found that α-HCG can be detected in PET buy not in normal islet cells, ct-HCG immunoreactivity was expressed by 5 of 28 (18%) in benign PET and 14 of 24 (58.3%) in malignant PET. Using in situ hybridization of α-HCGmRNA, a strong signal in PET was obtained. The clinico-pathological significance of α-HCG in PET was discussed.